Exploring stakeholders’ experiences of comprehensive geriatric assessment in the community and out-patient settings: a qualitative evidence synthesis - Christina Hayes; Christine Fitzgerald; Íde O’Shaughnessy; Brian Condon; Aoife Leahy; Margaret O’Connor; Molly Manning; Anne Griffin; Liam Glynn; Katie Robinson; Rose Galvin (BMC Primary Care, 2023)
Abstract Background Comprehensive Geriatric Assessment (CGA) is a multidimensional interdisciplinary process that addresses an older adult’s biopsychosocial capabilities to create an integrated and co-ordinated plan of care. While quantitative evidence that demonstrates the positive impacts of CGA on clinical and process outcomes has been synthesised, to date qualitative research reporting how older adults and service providers experience CGA has not been synthesised. This study aimed to systematically review and synthesise qualitative studies reporting community-dwelling older adults’, caregivers’ and healthcare professionals’ (HCP) experiences of CGA in the primary care and out-patient (OPD) setting. Method We systematically searched five electronic databases including MEDLINE, CINAHL, PsycINFO, PsycARTICLES and Social Sciences Full Text targeting qualitative or mixed methods studies that reported qualitative findings on older adults’, caregivers’ and HCPs’ experiences of CGA in primary care or out-patient settings. There were no language or date restrictions applied to the search. The protocol was registered with the PROSPERO database (Registration: CRD42021283167). The methodological quality of the included studies was appraised using the Critical Appraisal Skills Programme checklist for qualitative research. Results were synthesised according to Noblit and Hare’s seven-step approach to meta-ethnography, which involves an iterative and inductive process of data synthesis. Results Fourteen studies were included where CGA was completed in the home, general practice, out-patient setting in acute hospitals and in hybrid models across the community and hospital-based OPD settings. Synthesis generated four key themes: (1) CGA is experienced as a holistic process, (2) The home environment enhances CGA, (3) CGA in the community is enabled by a collaborative approach to care, and (4) Divergent experiences of the meaningful involvement of older adults, caregivers and family in the CGA process. Conclusion Findings demonstrate that CGA in a home-based or OPD setting allows for a holistic and integrated approach to care for community-dwelling older adults while increasing patient satisfaction and accessibility of healthcare. Healthcare professionals in the community should ensure meaningful involvement of older adults and their families or caregivers in the CGA process. Further robustly designed and well reported trials of different models of community-based CGA informed by the findings of this synthesis are warranted.